Esensialitas Metode Stad (Student Teams Achievement Division) untuk Pendalaman Materi Bahasa Indonesia di Sekolah - Hasanah, Siti Nurhidayatul (EDUKASI: Jurnal Pendidikan Islam, 2015)
In the presence a portion student that declares for that Indonesian study really palls is fairly, since they have perceived can and forwarding material which unattractive so at second hand student become arrest deep frail that material. As teacher of Indonesian was necessarily feels happening learning problem all this time. So teacher necessarily tries do changes in Indonesian learning at within class. One of change which is done by use of method role play and STADS method (Student Teams Achievement division) in standart interest converses and reading. In learning Tells hobby, can be done by use of method role play so makes student more active. Method role play understanding language as skill of straightforward speaking with bases student life in masayarakat. Method role play well-matched being applied while teacher does speaking learning with aided with role card.